Internet for the youngest: computer usage and web design for the early school age children - Librenjak, Sara (Array, 2009)
In this paper we will talk about the Web usage practices and Web page design aimed at children of an early elementary school age. Learning about differences in understanding and using the Web should aid in the development of Web content for children. Thus research in opinions, practices and needs of the Internet's youngest users should today be considered a must, also in order to provide a better education about those topics. Data was collected through the field research in an elementary school in Zagreb. 90 students answered the questionnaire and additional 12 students were randomly selected for the interview.